Spatial networks differ when food supply changes: Foraging strategy of Egyptian fruit bats - Bachorec, Erik; Horáček, Ivan; Hulva, Pavel; Konečný, Adam; Lučan, Radek K; Jedlička, Petr; Shohdi, Wael M; Řeřucha, Šimon; Abi-Said, Mounir; Bartonička, Tomáš (PloS one, 2020)
Animals are faced with a range of ecological constraints that shape their behavioural decisions. Habitat features that affect resource abundance will also have an impact, especially as regards spatial distribution, which will in turn affect associations between the animals. Here we utilised a network approach, using spatial and genetic data, to describe patterns in use of space (foraging sites) by free-ranging Egyptian fruit bats (Rousettus aegyptiacus) at the Dakhla Oasis in Egypt. We observed a decrease in home range size during spring, when food availability was lowest, which was reflected by differences in space sharing networks. Our data showed that when food was abundant, space sharing networks were less connected and more related individuals shared more foraging sites. In comparison, when food was scarce the bats had few possibilities to decide where and with whom to forage. Overall, both networks had high mean degree, suggesting communal knowledge of predictable food distribution.
Keywords: Spatial Analysis; Animals; Female; Seasons; Egypt; Chiroptera; ženské pohlaví; stravovací zvyklosti; Animal Distribution; roční období; Animal Communication; Information Dissemination; Male; Feeding Behavior; Food Supply; komunikace zvířat; ekosystém; Ecosystem; zvířata; mužské pohlaví; prostorová analýza; rozšíření zvířat; šíření informací; zásobování potravinami